1999
DOI: 10.1007/s000110050479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin on N-formyl-methionyl-leucyl-phenylalanine (fMet-Leu-Phe)-stimulated production of reactive oxygen metabolites from normal human neutrophils

Abstract: These results suggest that elevated levels of insulin do not affect the NADPH-oxidase activity but, together with superoxide anions, interfere with myeloperoxidase availability and a subsequent myeloperoxidase-dependent generation of reactive oxygen metabolites in fMet-Leu-Phe-stimulated normal human neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Insulin seemed to also possess a down-regulating action on enzymes involved in ROS elimination, as shown in this study for MPO. It was also found that MPO activity was reduced by in vitro insulin treatment in the cell-free supernatant of healthy PMN [37] and was altered in noncontrolled diabetic patients [38]. In addition, intravenous insulin infusion to induce hypoglycemia in healthy humans provoked an increase in the PMN count with associated elevation in plasma PMN elastase concentration [39].…”
Section: Discussionmentioning
confidence: 98%
“…Insulin seemed to also possess a down-regulating action on enzymes involved in ROS elimination, as shown in this study for MPO. It was also found that MPO activity was reduced by in vitro insulin treatment in the cell-free supernatant of healthy PMN [37] and was altered in noncontrolled diabetic patients [38]. In addition, intravenous insulin infusion to induce hypoglycemia in healthy humans provoked an increase in the PMN count with associated elevation in plasma PMN elastase concentration [39].…”
Section: Discussionmentioning
confidence: 98%
“…Much work has been conducted to study the effects of hyperglycemia on the function of neutrophils [4] but knowledge on the effects of hyperinsulinemia on neutrophil function is scanty. In normal human neutrophils, physiological or moderately elevated levels of insulin was shown to stimulate chemokinesis [5,6] but to inhibit respiratory burst activation by the bacterial factor fMet-Leu-Phe [7]. The stimulating effect of insulin on neutrophil motility was found to be mediated through a tyrosine kinase and PI3-kinase-dependent signaling pathway [6].…”
Section: Introductionmentioning
confidence: 96%